Cutting Edge: IL-15-independent NK cell response to mouse cytomegalovirus infection - Sun, Joseph C. (2009)
Natural Killer (NK) cells respond rapidly during viral infection. The development, function, and survival of NK cells are thought to be dependent on Interleukin (IL)-15. In mice lacking IL-15, NK cells are found in severely decreased numbers. Surprisingly, following infection of IL-15- and IL-15Rα-deficient mice with mouse cytomegalovirus (MCMV), we measured a robust proliferation of Ly49H-bearing NK cells in lymphoid and non-lymphoid organs, capable of cytokine secretion and cytolytic function. Remarkably, even in Rag2(−/−) × Il2rg(−/−) mice, a widely used model of NK cell deficiency, we detected a significant number of NK cells one week after MCMV infection. In these mice, we measured a greater than 300-fold expansion of NK cells, which was dependent on recognition of the m157 viral glycoprotein ligand and IL-12. Together, these findings demonstrate a previously unrecognized independence of NK cells on IL-15 or other common-γ signaling cytokines during their response against viral infection.